MiR-146a alleviates inflammatory bowel disease in mice through systematic regulation of multiple genetic networks - Zhu, Fengting; Yang, Taotan; Ning, Mengmeng; Liu, Yang; Xia, Wei; Fu, Yan; Wen, Ting; Zheng, Mei; Xia, Ruilong; Qian, Ran; Li, Yang; Sun, Minxuan; et al. (Frontiers in Immunology, 2024)
Inflammatory bowel disease (IBD) is a multiple-genes-involved chronic disease and current available targeted drugs for IBD only deliver moderate efficacy. It's unknown whether one single gene systematical regulating IBD exists. Here we showed that the expression of miR-146a in colon was elevated in Dextran Sulfate Sodium (DSS)-induced IBD mice and patients with IBD. DSS induced dramatic body weight loss and much more rectal bleeding, shorter colon length and colitis in miR-146a knock-out mice than wild type (WT) mice. The miR-146a mimics alleviated DSS-induced symptoms in both miR-146a -/-and WT mice. Further RNA sequencing illustrated that deficiency of miR-146a de-repressed majority of DSS-induced IBD-related genes which cover multiple genetic regulatory networks in IBD, and supplement of miR-146a mimics inhibited expression of many IBD-related genes.